The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.7567/jjap.55.04ee09
|View full text |Cite
|
Sign up to set email alerts
|

Low power switching of Si-doped Ta2O5 resistive random access memory for high density memory application

Abstract: We report, for the first time, the resistive switching properties of Si-doped Ta2O5 grown by atomic layer deposition (ALD). The reduced switching current, improved on/off current ratio, and excellent endurance property are demonstrated in the Si-doped Ta2O5 resistive random access memory (ReRAM) devices of 50 nm tech node. The switching mechanism for the Si-doped Ta2O5 resistor is discussed. Si dopants enable switching layer to have conformal distribution of oxygen vacancy and easily form conductive filament. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Thus, in current investigation, we demonstrated the direct current density dependence on stoichiometry of tantalum oxide. Oxygen vacancies acting as traps allow to explain the low values of resistances for LRS and HRS states for TaO x ReRAM. ,, However, in ReRAM the typical values of LRS resistance are 6–8 kOhm, while HRS values are of the 200–300 kOhm. For the discussed TaO x films with maximum nonstoichiometry (Figure a), for the readout field ∼1 MV/cm the current densities are of the order of 10 2 A/cm 2 and this corresponds to the resistance ∼1 MOhm, for a memory dot of ∼1 μm 2 area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in current investigation, we demonstrated the direct current density dependence on stoichiometry of tantalum oxide. Oxygen vacancies acting as traps allow to explain the low values of resistances for LRS and HRS states for TaO x ReRAM. ,, However, in ReRAM the typical values of LRS resistance are 6–8 kOhm, while HRS values are of the 200–300 kOhm. For the discussed TaO x films with maximum nonstoichiometry (Figure a), for the readout field ∼1 MV/cm the current densities are of the order of 10 2 A/cm 2 and this corresponds to the resistance ∼1 MOhm, for a memory dot of ∼1 μm 2 area.…”
Section: Resultsmentioning
confidence: 99%
“…Stoichiometric tantalum oxide (Ta 2 O 5 ) dielectric films find wide applications in microelectronics due to their high dielectric constant (κ = 25–50), electrical strength, and good thermal and chemical stability. In the last years, the interest to tantalum oxide strongly increased due to its successful use in nonvolatile resistive random access memories (ReRAM) or/and memristors, especially after nonstoichiometric oxygen deficient tantalum oxide (TaO x ) based ReRAM was moved into production. , ReRAM is considered both for stand-alone data storage applications, as well as an embedded nonvolatile memory. Neuromorphic applications, in particular delegating a part of data processing to memories in computer architectures, are also considered. , Among various oxide-based resistive switching elements, devices based on TaO x exhibit excellent memory retention performance, switching speed, endurance (number of switching cycles), , and low power consumption. , The industrial tantalum oxide ReRAM is based on resistance changes in TaO x filaments formed in the stacked dielectric structures comprising TaO x and a stoichiometric Ta 2 O 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Yasuhara et al reported a TaOx based low operation current RRAM device by controlling the oxygen content of the resistance-switching material [12]. Kim et al systematically analyzed the influence of Si doping in Ta 2 O 5 -based RRAM device, and 10 µA operating current is achieved because of conformal distribution of oxygen vacancies (Vo) in resistive layer [13].…”
Section: Introductionmentioning
confidence: 99%
“…Both of these changes can potentially lead to promising doped oxides with low operating voltages, good retention, high endurance, as well as high ON/OFF ratio. Many studies have been conducted to explore the doping effect on resistive switching device performance. For example, Zhao et al from Stanford University and Zhao et al from Anhui University systematically studied the trend of V O formation energy in metal-doped TiO 2 and HfO 2 using first principle-calculations. The authors concluded that a larger difference in the number of valence electrons between the dopant and the host atom can cause more significant reduction in the V O formation energy near the dopants .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they also found that as the formation energy of V O decreases, the forming voltage and ON/OFF current ratio also decrease in metal-doped HfO 2 resistive switching devices. Besides metal dopants, the doping effect of nonmetal dopants such as H, N, C, and Si in memory switching oxides was also widely studied. , …”
Section: Introductionmentioning
confidence: 99%